The Role of Corporate Social Responsibility in Strengthening Social Legitimacy Through Zakat - Siti Muyasaroh; Nabrisi Rohid; Ahmad Ziddan Wildan Al-Islami; Mohammad Atiqurrahman (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The management of corporate zakat is becoming an increasingly essential part of the governance of Islamic philanthropic institutions, especially as CSR regulations and tax incentives strengthen their legal foundation and social legitimacy. This research is motivated by the need to understand how the Amil Zakat Institution, especially NU-Care LazisNU, responds to these external pressures and integrates zakat into sustainability strategies and institutional communication. A qualitative approach is employed through in-depth interviews with zakat managers, analysis of the institution's annual report, and a review of supporting documents to explore the institution's managerial practices, communication patterns, and partnerships. The results of the study indicate that CSR regulation is the primary factor ensuring that zakat management is conducted systematically, professionally, and with a long-term orientation. Tax incentives serve as an additional driver, strengthening institutions' capacity to expand social programs. NU-Care LazisNU employs a two-way communication model through digital media, annual reports, proposals, and cross-sector partnerships. Zakat is positioned as a strategic instrument that supports six program pillars: education, health, economy, da'wah, social welfare, and humanitarian aid. These findings confirm that corporate zakat has evolved into a modern governance practice that strengthens the moral legitimacy and social effectiveness of institutions